The Effect of Tax Avoidance on Company Value with Audit Quality as a Moderating Variable : Empirical Study on Mining Companies Listed on the IDX 2016 - 2021 - Rustati Aisya Aliana; Goenawan, Yohanes August (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To determine the effect of tax avoidance on company value with corporate governance proxied by audit quality as a moderating variable. Background Problems: When there is an increase in profits in the form of compensation for managers, companies with poor governance will experience a decrease in the level of tax avoidance that should be done for shareholders. Novelty: Testing in different year periods and different objects and adding moderating variables in determining the relationship of variables. Research Methods: This study is a type of quantitative research with purposive sampling with data testing used is linear regression analysis and moderate regression analysis (MRA). Findings/Results: Tax avoidance does not have a significant effect on company value with a significance level of 0.587. Corporate governance proxied by audit quality is able to weaken the relationship between tax avoidance and company value with a significance level of 0.001. Conclusion: In mining companies, tax avoidance is often carried out even though the audit quality is good in this study actually weakens the value of the company that is in the tax avoidance carried out.